Vega's Request : inter-departmental correspondence - Bolton, W. J.
011-0017-001 I.C.3 TRADES UNION CONGRESS GENERAL COUNCIL. INTER-DEPARTMENTAL CORRESPONDENCE. From W. J. BOLTON Department International To Sir WALTER CITRINE Date November 22, 1937. SUBJECT. Re: VEGA'S REQUEST. I.F.T.U. telephoned this afternoon in answer to our enquiry that these people had really come to Paris to attend a Spanish Refugees' Conference, and that they thought they would take the opportunity of meeting the I.F.T.U. Upon being shown the letter of invitation to the meeting on 7th and 8th December, they expressed themselves as satisfied, and did not press the matter. We answered that, as a matter of courtesy, the President was willing to see them in London, but the I.F.T.U. are of opinion that they will not require the Interview now, in the circumstances. [W.J.B] WJB/AC/182 292/946/11/17